Normative Values of Saccades and Smooth Pursuit in Children Aged 5 to 17 Years - Sinno, Solara; Najem, Fadi; Abouchacra, Kim Smith; Perrin, Philippe; Dumas, Georges (Journal of the American Academy of Audiology, 2020)
Background Pediatric oculomotor function can be evaluated via videonystagmography. Adult normative data for saccades and smooth pursuit tests cannot be used as a benchmark for pediatric patients because children's peripheral and central systems continue to mature throughout adolescence.Purpose The purpose of this study was to establish normative data for saccade and smooth pursuit tests that can be used clinically in the assessment of vestibular and neurological disorders in children, and to investigate the effect of age and eye movement direction (left/right) on tests parameters.Research Design The present study is prospective cross-sectional study.Study Sample A total of 120 healthy children were recruited and equally distributed according to age and gender to each of the following groups: 5-8, 9-11, 12-14, and 15-17 years old. Participants had to pass a comprehensive otological and neurological assessment prior to inclusion in the study. Each subject underwent saccade and smooth pursuit testing.Data Collection and Analysis Saccade latency, velocity and accuracy/precision, and smooth pursuit gain were analyzed across groups using a two-way repeated measure multivariate analysis of variance (MANOVA).Results Saccadic latency was longer in the youngest group aged 5-8 years old (305 ± 48 msec) in comparison to children aged 9-11 years old (276 ± 22 msec) (P = 0.017), 12-14 years old (252 ± 34 msec) (P = 0.001) adolescents 15-17 years (256 ± 33 msec) (P = 0.001). Age did not affect the results of saccadic velocity and accuracy/precision. Saccade parameters (latency, velocity, accuracy/ precision) were not affected by oculomotor direction (left vs. right). Smooth pursuit gain increased from 0.63 in children aged 5-8 years old to 0.85 in children aged 15-17 years (P = 0.0001). The percentage of gain asymmetry was significantly different in the youngest two groups.Conclusion Saccade latency decreased as age increased. Smooth pursuit gains increased with increased age. Saccade velocity and accuracy/precision did not change significantly from ages 5-8 to 15-17 years of age. These data provide normative values for pediatric oculomotor evaluation and suggest that saccade and pursuit pathways may mature at different rates.
Keywords: maturation; pediatric; saccade; smooth pursuit; videonystagmography